Pricing of digital services as an effectual co-creative process - Karami, Masoud; Ojala, Arto; Laatikainen, Gabriella (Taylor & Francis, 2022)
Entrepreneurs have to price their innovations under the unpredictability of customers’ reactions. While predictive pricing methods are prevalent in business-to-business pricing literature, we argue for the critical importance of control-oriented pricing strategies for digital services. By applying effectuation theory, our study investigates how entrepreneurs co-create their pricing strategies for their digital services as a co-evolutionary, iterative process with their customers. We found that pricing is the co-evolutionary process where entrepreneurs learn from their interactions with customers and use this knowledge to develop and improve their pricing practices further. The findings contribute to behavioural pricing literature by explaining pricing strategy formation as a co-creative process that focuses on interactions rather than predictive actions.
Keywords: Co-creative pricing; digital services; Effectuation; uncertainty; fi=Kansainvälinen liiketoiminta|en=International Business|